ISTILAH DALAM PROSES PEMBUATAN WAYANG KULIT DI DUSUN KARANGASEM, DESA WUKIRSARI, KECAMATAN IMOGIRI, BANTUL, YOGYAKARTA - Riffai Riffai; Sudartomo Macaryus (CARAKA, 2018)
The purpose of this study is as follows. (1) Describe the formation of the term in the process of making wayang kulit in Karangasem Hamlet, Wukirsari Village, Imogiri District, Bantul, Yogyakarta. (2) Describe the term form in the process of making wayang kulit in Karangasem Hamlet, Wukirsari Village, Imogiri District, Bantul, Yogyakarta. (3) Describe the meaning of the term in the process of making wayang kulit in Karangasem Hamlet, Wukirsari Village, Imogiri District, Bantul, Yogyakarta. The data in this research are the terms in the process of making wayang kulit in Karangasem Hamlet, Wukirsari Village, Imogiri District, Bantul, Yogyakarta. Sources of research data is sourced from the spoken language taken from the interview with the speakers of leather puppets. Data collection method in this research is simak method and skill method. Methods of reference using basic techniques tapping with advanced techniques in the form of technically skilled libat, recording techniques, and record techniques. Ability to use basic tenet fishing method with advanced technique in the form of fishing technique meet face. Data analysis using method of padan and Agih Method. The method is in combination with referential and translational techniques; and a method with a technique for direct elements. The method of presenting the result of data analysis is done by informal method. The results of this study are as follows. (1) The formation of the term in the process of making wayang kulit in Dusun Karangasem, Wukirsari Village, Imogiri District, Bantul, Yogyakarta is by using affixation, reduplication, composition, and abreviation. (2) The term form in the process of making wayang kulit in Karangasem Hamlet, Wukirsari Village, Imogiri Subdistrict, Bantul, Yogyakarta is a term which is in the form of basic, berretical form, reproduction, compound form, and acronym form. (3) The meaning of the term in the process of making wayang kulit in Karangasem Hamlet, Wukirsari Village, Imogiri Sub-district, Bantul, Yogyakarta is (a) lexical meaning, (b) grammatical meaning of affixation with prefix /N-/, /di-/ , and /ka-/, suffix /-an/, and affix /N-/-/-i/; the grammatical meaning of reduplication, and the grammatical meaning of abreviation; and (c) idiomatic meanings.